ENACTING THE GODS: THE PERFORMANCE OF HAOBA NURABI EPISODE IN THE LAI HARAOBA OF MANIPUR - Premchandra, Kshetrimayum (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This paper examines the performance of the Haoba Nurabi episode in the Meitei Lai Haraoba of Manipur. It attempts to delve into the intricate rituals of Lai Haraoba, a celebration that combines elements such as dance, music, sports, and sacred ceremonies to honour the presiding deities. The paper also provides insights into the performance space known as the laipung, shedding light on the staging and realisation of this traditional performance style. Throughout this paper, the terms drama, theatre, and performance are used interchangeably with due emphasis on spectator experience rather than the technicalities of the terms and methodological challenges. The episode under consideration reenacts the interactions between the divine lovers Haoba and Nurabi, who initially fail to recognise each other, which offers moments of humour and clever dialogues while performing activities like tilling, sowing, and harvesting. With multiple constituent elements making this propitiatory festival an entity unto itself, Lai Haraoba holds significance within India’s broader landscape of performance traditions. And Haoba Nurabi sets itself apart within the ritual-rich ambience of the Lai Haraoba festival by exhibiting structural and presentational similarities to contemporary drama.